Optimisation d'exploitation d'un échangeur de chaleur tubulaire dans le processus de séparation de pétrole brut - الحاتمي, نسيم; العبيد, وليد (university of Eloued جامعة الوادي, 2018)
يهدف هذا البحث إلى دراسة نقص في المردود للمبادلات الحرارية ومعرفة الأسباب التي تؤدي لهذا المشكل . إن النقص في المردود يؤدي إلى خسارة كبيرة سواء في الطاقة أو ضياع في الكتلة والتي تؤدي سلبا على معالجة النفط الخام وخسارة مادية تكمن في نقص الإنتاج المرغوب فيه. ولقد اعتمدنا في منهاجنا هذا على المبادل الحراري 03HX1111في مجموعة بئر السبع لمعالجة النفط الخام لمنطقة حاسي مسعود وبعد دراستنا وتحليل النتائج وجدنا أن هناك كمية من المائع لا تصل إلى الفاصل 03V1112مما أدى إلى نقص في درجة الحرارة وأثرت سلبا على عملية الفصل . وقد كانت النتائج المحصل عليها بواسطة المحاكاة باستعمالHYSYS10 مرضية تقريبية للنتائج المحسوبة مع وجود اختلافات بسيطة في درجة حرارة السائل الساخن . يمكن لنا بدراسة أي ظاهرة أو فكرة ما من خلال برنامجHYSYS في اقل وقت ممكن وإعطاء نتائج مقبولة . This dissertation aims at studying the shortage in the revenue of temperature exchanges and knowing the reasons that lead to this problem. The shortage in the revenue leads to a large loss in either energy or loss in the mass, which negatively affect the treatment of crude oil and concrete loss in the desired production.. In our method, we adopted the temperature exchanger 03HX1111 in the Beer Sbea group of procesings the crude oil in Hassi Messaoud. After our study and analysis of the results, we found that there was a fluid that did not reach 03V1112, which led to a lack of temperature and negatively affected the separation process. The results obtained by the simulation using HYSYS10 were approximate to the calculated results with slight differences in the temperature of the hot liquid. We can study any phenomenon or idea through the HYSYS program in the shortest possible time and get acceptable results
مذكرة ماستر تخصص هندسة التكرير
Keywords: température, exchanges, HYSYS, crued oil,revenue,separation; درجة الحرارة ،المبادل الحراري ،محكاة ،النفط الخام ،المردود ،فصل